2021
DOI: 10.1177/15330338211056478
|View full text |Cite
|
Sign up to set email alerts
|

Post-transplantation Fluorine-18 Fluorodeoxyglucose Positron Emission Tomography in Patients with Lymphoblastic Lymphoma is an Independent Prognostic Factor with an Impact on Progression-Free Survival but not Overall Survival

Abstract: Purpose: In the present study, we mainly aimed to evaluate the prognostic value of 2-deoxy-2-[18F]fluoro-D-glucose ([18F]F-FDG) positron emission tomography (PET)/computed tomography (CT) after allogeneic stem cell transplantation (allo-SCT) in lymphoblastic lymphoma (LBL) patients using Deauville Scores (DS). Materials and Methods: A total of 63 LBL patients who benefited from 18F-FDG PET-CT after allo-SCT in our institution between April 2010 and August 2020 were enrolled in this retrospective study. These a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Dai et al discovered that PET/CT after allo‐HSCT was a powerful predictor of PFS but not of OS in 67 patients with LBL. 44 Sun et al demonstrated that PET/CT before HSCT could not predict PFS or OS but that the post‐HSCT PET/CT‐positive group had a greater risk compared to the PET/CT‐negative group among 21 consecutive patients with relapsed or refractory T‐LBL who underwent HSCT. 45 This paradoxical outcome may be attributable to differing time points of PET/CT evaluation before HSCT.…”
Section: Discussionmentioning
confidence: 99%
“…Dai et al discovered that PET/CT after allo‐HSCT was a powerful predictor of PFS but not of OS in 67 patients with LBL. 44 Sun et al demonstrated that PET/CT before HSCT could not predict PFS or OS but that the post‐HSCT PET/CT‐positive group had a greater risk compared to the PET/CT‐negative group among 21 consecutive patients with relapsed or refractory T‐LBL who underwent HSCT. 45 This paradoxical outcome may be attributable to differing time points of PET/CT evaluation before HSCT.…”
Section: Discussionmentioning
confidence: 99%
“…Dai et al [44] proposed that the sensitivity, specificity, positive predictive value, negative predictive value, and accuracy of 18 F-FDG PET-CT in patients undergoing allogeneic hematopoietic stem cell transplantation were 100%, 92.2%, 75.0%, 100%, and 93.7%, respectively. Moreover, it can be used to evaluate the progression-free survival (PFS) of patients, which can provide an important basis for the selection of subsequent treatment options for patients with lymphoblastic lymphoma.…”
Section: Application Basis and Background Of 18 F-fdg Pet/ctmentioning
confidence: 99%
“…Moreover, 2-deoxy-2-[ 18 F]fluoro-D-glucose positron emission tomography/computed tomography ( 18 F-FDG PET-CT) has been widely used for staging, restaging, aggressiveness evaluation, and response monitoring of lymphoma since PET-CT was incorporated into the guidelines for lymphoma in 2007 [ 6 , 7 ]. Our preliminary studies [ 8 , 9 ] have shown that post-transplantation PET is helpful for the prognostic assessment of lymphoma patients.…”
Section: Introductionmentioning
confidence: 99%